Effect Of Mocaf Substitution And Beetroot Flour Addition On Dimsum Wrapper Hedonics - Mirna Almirasari; Asrul Bahar (Universitas Negeri Padang, 2026)
Dumpling wrappers are the outer layer that encloses the filling and are commonly referred to as wonton wrappers, which are generally made from wheat flour. In this study, dumpling wrappers were produced using modified cassava flour (mocaf) with the addition of beetroot flour. This study aimed to determine the effect of mocaf flour substitution and beetroot flour addition, as well as to identify the dumpling wrapper formulation with the highest level of preference among panelists based on the combination of these treatments. This study employed a Completely Randomized Design (CRD) with a 3×2 factorial pattern, resulting in six treatment combinations. The treatments consisted of mocaf flour substitution at levels of 30%, 40%, and 50%, and beetroot flour addition at levels of 20% and 30%. A hedonic test was conducted involving 50 untrained panelists using a five-point scale to evaluate color, aroma, taste, texture, and shape as response variables. The data were analyzed using two-way ANOVA to examine the main effects and interactions, followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level (p < 0.05). The results indicated that mocaf flour substitution had a significant effect on color, aroma, texture, shape, and taste (p < 0.05), whereas beetroot flour addition did not significantly affect all sensory attributes (p > 0.05). The interaction between mocaf flour substitution and beetroot flour addition showed a significant effect on color, aroma, texture, and shape, but no significant effect on taste. The best treatment was obtained at 40% mocaf flour substitution and 30% beetroot flour addition, resulting in dumpling wrappers with the best sensory quality.